Realization of Rectangular Artificial Spin Ice and Direct Observation of High Energy Topology. Issue 1 (December 2017) - Ribeiro, I.; Nascimento, F.; Ferreira, S.; Moura-Melo, W.; Costa, C.; Borme, J.; Freitas, P.; Wysin, G.; Araujo, C.; Pereira, A.
Abstract In this work, we have constructed and experimentally investigated frustrated arrays of dipoles forming two-dimensional artificial spin ices with different lattice parameters (rectangular arrays with horizontal and vertical lattice spacings denoted bya andb respectively). Arrays with three different aspect ratiosγ  = a /b  =  $$\sqrt{{\bf{2}}}$$ 2, $$\sqrt{{\bf{3}}}$$ 3 and $$\sqrt{{\bf{4}}}$$ 4 are studied. Theoretical calculations of low-energy demagnetized configurations for these same parameters are also presented. Experimental data for demagnetized samples confirm most of the theoretical results. However, the highest energy topology (doubly-charged monopoles) does not emerge in our theoretical model, while they are seen in experiments for large enoughγ . Our results also insinuate that the string tension connecting two magnetic monopoles in a pair vanishes in rectangular lattices with a critical ratioγ  = γ c  =  $$\sqrt{{\bf{3}}}$$ 3, supporting previous theoretical predictions.